The virgin unmask'd / by Henry Fielding. - Fielding, Henry, 1707-1754. (Tufts University. Tisch Library., 2015)
1 online resource (pages [120]-141); Caption title.; Originally appeared under title: The old man taught wisdom; or, The virgin unmask'd.; Published in A Collection of the most esteemed farces and entertainments performed on the British stage, v. 2.; Without the music.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.